(untitled) (REMUNOM, 2026)
The demand for floral resources, high energy expenditure during forages and the limited number of flowers may result in different levels of inter- and intraspecific competition among bees. This work aimed to establish the categories of intra and interspecific interactions involving species of bees in forages in the flowers of Solanum lycocarpum. The foraging activity of the bees was recorded for 12 days not necessarily consecutive during the full flowering process, between 6: 00h and 17: 15h in the first 15 minutes of each hour, totaling 132 observation hours. The number of flowers visited and the intra and interspecific agonistic interactions were recorded. Faunal analysis was developed to define the classes, abundance, frequency, consistency and dominance of the species. Of the 10 species of bees recorded were classified as constant Centris scopipes; Augochlora sp; Augocloropsis sp; Exomalopsis fulvofasciata; Bombus sp; Oxaea flavescens. 401 aggressive encounters were recorded, contemplating the different agonistic interactions. These interactions were observed only among the species O. flavescens, E. fulvofasciata, Augochlora sp and Augochloropsis sp. The species O. flavescens and E. fulvofasciata were more frequently involved in combats of which they were winning, thus exerting dominance in relation to the foraging area, being the ’flower confrontation’, the most constant action, both in the intra and Interspecific. The species O. flavescens and E. fulvofasciata were more frequently involved in combats of which they were winning, thus exerting dominance in relation to the foraging area, being the ’flower confrontation’, the more constant action, both in intra and interspecific interactions. It is believed that the possible reduction of resource availability in the area, caused by deforestation of the forest fragment, may have contributed to the intensification of competition and conflicts among bees.